Synthesis and Characterization of Magnetic Nanomaterials with Adsorptive Properties of Arsenic Ions - Agnieszka Wojciechowska; Zofia Lendzion-Bieluń (Molecules, 2020)
A new synthesis method of hybrid Fe3O4/C/TiO2 structures was developed using microwave-assisted coprecipitation. The aim of the study was to examine the effect of the addition of glucose and titanium dioxide on adsorptive properties enabling removal of arsenic ions from the solution. The study involved the synthesis of pure magnetite, magnetite modified with glucose and magnetite modified with glucose and titanium dioxide in magnetite: glucose: titanium dioxide molar ratio 1:0.2:3. Materials were characterized by XRD, FT-IR, and BET methods. Magnetite and titanium dioxide nanoparticles were below 20 nm in size in obtained structures. The specific surface area of pure magnetite was approximately 79 m2/g while that of magnetite modified with titanium dioxide was above 190 m2/g. Obtained materials were examined as adsorbents used for removal As(V) ions from aqueous solutions. Adsorption of arsenic ions by pure magnetite and magnetite modified with titanium dioxide was very high, above 90% (initial concentration 10 mg/L), pH in the range from 2 to 7. The preparation of magnetic adsorbents with a high adsorption capacity of As(V) ions was developed (in the range from 19.34 to 11.83 mg/g). Magnetic properties enable the easy separation of an adsorbent from a solution, following adsorption.